Issues in school web atlas use: The prototype atlas of Rio Claro — Brazil - da Silva Ramos, Cristhiane; Cartwright, William; de Almeida, Rosângela Doin [UNESP] (Springer Nature, 2008)
This chapter describes a research programme that proposed an open-standard methodology for publishing Brazilian local school atlases on the Internet. One of the aims of the research was to contribute to foster the use of educational media in computer laboratories provided by the Brazilian government to public schools. The methodology proposed in this research was based on the use of HTML, SVG and Java Script to create Brazilian local school atlases on the Web. The School Atlas of Rio Claro (Sao Paulo State — Brazil) was used as the primary source of information to create a prototype Web atlas using the methodology proposed. The prototype was tested with a group of primary school teachers — the users. The results demonstrated that the teachers were keen to interact with the product and, although reproducing some common practices of paper map use, they revealed a deep interest in using the Internet as an educational medium.